Les monnaies athéniennes aux ve-ive siècles av. n. è., des mines du Laurion au marché de la Cité - Christophe Flament (Mélanges de la Casa de Velázquez, 2018)
In this paper we propose to trace the process of transformation undergone by silver at Athens, from its mining in Laurion to the minting of the famous owl coins. First we shall attempt to define the lower threshold of profitability of the mining sector from an estimation of the various costs associated with mineworking. Second, we shall seek to clarify the relationships between mining activity and monetary production by means of a thoroughgoing examination of a number of epigraphic documents dealing with coin manufacture, not only at Athens but also at Delphi. This examination shows that at Athens, mining impresarios must have had the option of taking their mined silver to the mint for processing into coins. This prompts two major conclusions: firstly, that it was the mining impresarios who dictated the rate and scale of minting; and secondly, it was likewise they who put the vast majority of newly-minted coins into circulation.